Molecular Mechanism in Epithelial-Mesenchymal Transition (EMT) and Fibrosis (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue of the International Journal of Molecular Sciences (IJMS), entitled “Molecular Mechanism in Epithelial-Mesenchymal Transition (EMT) and Fibrosis”, collected 15 original research papers (5 reviews and 10 articles) written by a panel of experts from different countries who highlight recent advances in the EMT process.Navigating the complex field of EMT, this Special Issue introduces the current understanding of the underlying mechanisms of EMT in the evolution and progression of fibrogenesis and discusses potential strategies for attenuating EMT to prevent and/or inhibit fibrosis.Overall, the 15 scientific articles in this Special Issue of the International Journal of Molecular Sciences provide valuable insights into the complex mechanisms governing the EMT process linked to fibrosis and have highlighted the potential of novel therapeutic strategies. In the last few years, the field of EMT has shown considerable promise, and there is still much to be learned. As our understanding continues to grow, we hope that this Special Issue serves as a catalyst for further research and innovation in this developing field.